From Transience to Immanence: Consumption, Life-Cycle and Social Mobility in Kerala, South India - FILIPPO OSELLA and CAROLINE OSELLA (Modern Asian Studies 33, 4 (1999), pp. 9891020., 1999)
In this paper, we explore some ways through which the adoption of specirc consumption practices enables members of a South-Indian ex-untouchable community, Izhavas within Kerala, to objectify and rederne their self-perceived and other-perceived social position, and to concretize and make sense of their attempts to achieve generalized upward mobility. Located within individual, familial and group mobility strategies and developmental cycles, consumption assumes a long-term dimension, oriented towards present and future. Consumption practices also take on a normative aspect: youthful orientations towards transience and ephemerality should be replaced by a mature demeanour directed towards duration and permanency, and achievement of householder status. `Householders' negotiate their paths through a complex consumer culture where values of transience and durability articulate with a local/foreign continuum. The labouring poor, whose consumption is severely limited, remain unable, in the eyes of the majority, to attain mature householder status. While Dalit castes withdraw into virtuosity in arenas such as fashion, labouring Izhavas struggle unsuccessfully to maintain distinction and join the mainstream.